Mediastinal Parathyroidectomy: Preoperative Management of Hyperparathyroidism - Sagan, Dariusz; Tarach, Jerzy S.; Nowakowski, Andrzej; Klatka, Maria; Czekajska-Chehab, Elżbieta; Drop, Andrzej; Chrapko, Beata; Klatka, Janusz (IntechOpen, 2012)
None